2022
DOI: 10.1088/2632-072x/ac54c3
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence complex networks

Abstract: Complex networks, which constitute the main subject of network science, have been wide and extensively adopted for representing, characterizing, and modeling an ample range of structures and phenomena from both theoretical and applied perspectives. The present work describes the application of the real-valued Jaccard and real-valued coincidence similarity indices for translating generic datasets into networks. More specifically, two data elements are linked whenever the similarity between their respective feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…As described above, the modules extracted from the original document need to be interconnected according to their content similarity. In the present work, we employ the coincidence similarity index [5,6,38] for that finality, in order to perform more selective and sensitive similarity quantification.…”
Section: The Coincidence Similarity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, the modules extracted from the original document need to be interconnected according to their content similarity. In the present work, we employ the coincidence similarity index [5,6,38] for that finality, in order to perform more selective and sensitive similarity quantification.…”
Section: The Coincidence Similarity Indexmentioning
confidence: 99%
“…In order to integrate the complementary characteristics of the two previous indices, the Coincidence similarity index (C) has been described in [5,38,45], corresponding to the product between the Jaccard (equations ( 1) and ( 2)) and Interiority (equation ( 3) and ( 4)) indexes, i.e. :…”
Section: The Coincidence Similarity Indexmentioning
confidence: 99%
“…The Coincidence similarity Index [10][11][12] has been described as a measure to determine the similarity between virtually any type of mathematical entity, taking into account both the Jaccard and the Interiority (or overlap [21]) indices. This approach is motivated by the relative interiority between the compared sets not being captured by the Jaccard index [10], as well as by the need to generalize the Jaccard index to real-valued structures, including possibly negative values.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…The present work aims to study this interesting and relevant problem using the recently proposed coincidence similarity methodology [10][11][12][13]. In addition, we provide a simple but effective method for generating trees with diverse properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many scholars have been attracted to studying social networks. Through the study of community structure, scholars have revealed the general characteristics of complex networks and promoted the in‐depth analysis of network relationships (da Fontoura Costa, 2022). And generally, users appear in multiple communities at the same time, that is, overlapping users appear, thus forming overlapping communities (Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%